LEXICAL VARIATIONS OF THE AGRICULTURAL LEXICON “PLOW” IN BANDUNG REGENCY - Deanty Rumandang Bulan; Dani Hermawan; Rae Dadela (Universitas Islam Sumatera Utara, 2023)
This study presents the sociolinguistic study on lexical variations of the agricultural lexicon “plow”. The study aims to elaborate on how the lexical variations are constructed morphologically and also explain how sociolinguistic factors affect those variations. The study is conducted by means of descriptive qualitative method. The data for this study were extracted from a register of the agricultural corpus that was created by recording and transcribing the farmers’ conversations in Bandung Regency. The findings show that the lexical variations for ‘wuluku’ or “plow” in Bandung Regency are dominated by the agricultural lexicons that are related to agricultural tools and other agricultural activities. Morphologically, in the speakers’ daily utterances, the variations for lexicons “plow” have been used attached to the prefixes di- and N- that function to create a verb. From the sociolinguistics view, it also appears that some variations come from adopting the Indonesian lexicon as the result of bilingual/multilingualism in the community.